PERFORMA PENGGUNAAN EBI PADA STATUS FACEBOOK WALIKOTA DI SUMATERA BARAT - Rizaldi, Muhammad Okto; Juita, Novia; Ngusman, Ngusman (Jurnal Bahasa dan Sastra, 2018)
This study was conducted to describe the performance of the use of EBI on the status of Facebook mayor in West Sumatera. This research is a qualitative research using descriptive method. The data research in the form of writings written by some mayors in West Sumatera through Facebook account. In this research, author focuses some writings from the Mayor of Padang, the Mayor of Padang Panjang, the Mayor of Payakumbuh, and the Mayor of Solok. Data collection is using documentation method, that is: (1) printscreened writings the Mayor of Padang (period 2016—2017), the Mayor of Padang Panjang (period 2016—2017), the Mayor of Payakumbuh (period 2016—2017), and the Mayor of Solok (period 2015—2016); (2) transcribes all the Facebook posts; and (3) observe and determine the data that includes the performance of EBI. The exanubatuib of data validation in this research uses a detailed description technique. Data are analyzed with this following steps. (1) identify and transcribe the data, (2) classify, (3) calculate, (4) interpret the data, and (5) conclude the data. The conclusion of this study is the performance of Indonesian in terms of use of EBI on Facebook mayor in West Sumatra is very low (16.4%) of 499 speeches. The biggest mistake is in the use of capital letters and the smallest is in the use of quotation mark one.Keywords: EBI, language error, spelling, mayor, Facebook